Threats and Legal Protection of Personal Data Combined in E-Commerce Transactions Based on Personal Data Protection Law in Indonesia - Tegar Islami Putra; Nurul Fibrianti (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2024)
The dynamics of Indonesian trade are becoming more complex as time goes on, and one form of this development is digitalization. Although it has a positive impact, trade digitization also has a negative impact on different points of view, one of which is the threat in terms of combined personal data. Combined personal data is one type of personal data that is protected by the state through legal protection, so that the state guarantees people’s personal data. This scientific research uses one part of the grand method, namely Library Research which is based on literature or literature. The results of the research show that there are three forms of threats to people’s personal data combined in e-commerce transactions, especially in the use of IP Address, namely threats to geographic location tracking, unauthorized use and opening of personal data, and Distributed Denial of Service (DDoS) attacks. In the legal space in Indonesia, the three threats themselves do not yet have further rules related to the form and mechanism of protection and have different arrangements as a form of protection. Law Number 27 of 2023 concerning Personal Data Protection, Law Number 19 of 2016 amending Law Number 11 of 2008 concerning Electronic Information and Transactions, and Government Regulation of the Republic of Indonesia Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions. Based on this research, it is necessary to provide legal rules related to the form and mechanism of protecting a person’s IP Address as one type of personal data in Indonesia.